Leito fixo com reversão do ar de secagem: estudo experimental e numérico da secagem de Alumina - Genaro, Luana Boger (Universidade Federal de São Carlos, 2021)
Drying is a high-energy consumption process with applications in several industrial areas. The necessity of efficient processes increases the development of control, monitoring and optimization systems. As an engineering approach, these technologies can be possible using mathematical models to predict the behavior of the system. The aim of this research was to evaluate the two-phase mathematical model proposed by Massarani and Silva Telles (1992) for the prediction of the drying of alumina in a thick layer fixed bed, in the drying with and without the airflow reversal. Were used as porous medium spheres of alumina, initially saturated with water, with an average particle diameter of 3.2 ± 0.2 mm and 7.1 ± 0.7 mm. Transient temperature and moisture content were obtained for different axial positions of the bed during the drying. The experiments were performed using air temperatures of 40, 50 and 60 °C and air velocity of 2.7 m/s. The effects of the reversal parameters were investigated using an initial time of reversion application of 10 min with intervals ranges of 10, 30 and 50 min. The results showed a reduction in the heterogeneity of the bed and an increase in the specific energy consumption for the process with airflow reversal. It was found that the application of the airflow reversal reduced the bed temperature and moisture gradients, when compared with the conventional drying using an upward airflow. The study of the thin layer mathematical models showed that the drying rate proposed by the Lewis's model was sufficient to represent the phenomena and was used in the mathematical modeling of the thick layer fixed bed drying. The parameters of the diffusive model with convective boundary condition, indicated that the effects of internal and external resistance of mass transfer were important for the operational conditions used. The results obtained from the simulation of the drying of alumina using the two-phase model of Massarani and Silva Telles (1992), showed a good qualitative representation of the thermal and moisture behavior. Relative average absolute errors obtained between the experimental and the simulated temperatures were of 2.38 to 11.87 % and from 1.70 to 6.59 % for the drying with and without air flow reversal, respectively. For the moisture content at different axial positions, the errors were obtained from 7.66 to 33.18 % and 11.33 to 28.94 % for the drying with and without airflow reversal, respectively. The two-phase model of Albini (2019) adapted from Massarani and Silva Telles (1192) was used to predict the temperatures and moisture content for barley grains drying with airflow reversal in a thick layer fixed bed. For this grain, were obtained relative average absolute errors ranging from 1.7 to 7.0 %.
Fixed bed drying with airflow reversal: experimental and numerical study of Alumina drying
Keywords: Secagem; Leito Fixo; Reversão; Modelo matemático; Alumina; Drying; Fixed Bed; Airflow reversal; Mathematical model; Alumina; ENGENHARIAS::ENGENHARIA QUIMICA